The Essential Martin & Inge Riebeek : a decade of video portraits. - Riebeek, Martin; Riebeek, Inge ([Breda] : The Eriskay Connection, 2020)
The Essential reveals the ways in which we are unique, but also the similarities we share, despite our differences. Artists Martin and Inge Riebeek have been actively collecting stories from people around the world since 2010. The people they portray tell about what matters most to them, or what is essential in their lives. The resulting body of work thus far contains more than 600 video portraits of individuals from 23 countries. This book is a celebration of this past decade of work by the Riebeeks. It gives an overview of the video portraits and transcripts of the subjects' personal and revealing monologues, in turn accompanied by additional anecdotes and insights from the artists.
Subtitle from cover.
kunstcatalogus
Keywords: Riebeek, Inge; Riebeek, Martin